Comparative Metagenomic Study of Rhizospheric and Bulk Mercury-Contaminated Soils in the Mining District of Almadén - González, Daniel; Robas, Marina; Fernández, Vanesa; Bárcena, Marta; Probanza, Agustín; Jiménez, Pedro A. (Frontiers in Microbiology, 2022)
Soil contamination by heavy metals, particularly mercury (Hg), is a problem that can seriously affect the environment, animals and human health. In this study, a metagenomic analysis using Shotgun was performed on the soils of the Almadén mining region (Ciudad Real, Spain) to expand our knowledge of the microorganisms that develop in these environments, their interactions and the assessment of their potential use in the bioremediation of these contaminated soils. A bioinformatic analysis of the sequences was performed. With these sequences, a taxonomic identification was performed on the microorganisms together with a functional grouping of the genes they carry. The most abundant taxa were those of Actinobateria and Alphaproteobac-teria, recognizing that roots have a selective effect on the rhizospheric communities. A search was conducted for Hg resistance (mer genes and efflux pumps) and response to abiotic stress (salinity, desiccation, and contaminants), nitrogen metabolism and plant growth promotion (PGP genes). Likewise, an analysis was carried out on the sequences belonging to antibiotic resistance genes with clinical relevance, which may have been acquired due to the high abiotic pressure of Hg. At a functional level, it is clear that the mechanisms of resistance to antibiotics and other toxic compounds point to their co-choice in contaminated environments.